PENDIDIKAN KOGNITIF DAN AFEKTIF DAGUSIBU UNTUK PENCEGAHAN RESISTENSI ANTIBIOTIK DI SMA SURABAYA - Abhimata Paramanandana; Dini Retnowati; Andang Miatmoko; Dewi Isadiartuti; Sugiyartono1; Mohammad Agus Sjamsur Rijal; Dwi Setiawan; Esti Hendradi; Tutiek Purwanti; Noorma Rosita; Dewi Melani Hariyadi; Tristiana Erawati; Ardhani Dwi Lestari1; Helmy Yusuf; Retno Sari (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Antibiotics are not only used for humans, but also often used for cattle and livestock which are then been consumed by humans. This over prescribed and missed used of antibiotic is a major factor in antibiotic resistance. Antibiotic resistance is a condition where bacteria are unable to be treated with antibiotics. In fact, the use of antibiotics is the first response in curing infectious diseases (by bacteria) and preventing infectious diseases spreading. With antibiotic resistance, preventing infectious diseases by bacteria became harder. This community service activity came up with a slogan "Antibiotic Resistence Awareness Movement" was carried out in Surabaya 10 Public High Schools and Surabaya 17 Public High Schools with 60 students per school using several methods, namely: (a) giving lecture material using LCD projectors ) the implementation of poster making competitions, and (c) poster presentations that have been made that are accompanied by question and answer, and (d) evaluation activities in the form of written tests covering pre-test and post-test. Concerning the results of posters results, poster presentations and improving the results of this posttest can be concluded as a result of an increase in understanding and or knowledge of students of SMA 10 and SMA 17 Surabaya